A novel calreticulin-related molecule that interacts with bacteria and enhances host resistance against bacterial infection in black rockfish, Sebastes schlegeli. Issue 93 (October 2019) - Wang, Guang-hua; Li, Zhao-xia; Guo, En-mian; Wang, Jing-jing; Zhang, Min; Hu, Yong-hua
Abstract: Calreticulin (CRT) is a highly conserved and multi-functional protein with diverse localizations. CRT has lectin-like properties and possesses important immunological activities in mammalian. In teleost, very limited studies on CRT immunologic function have been documented. In the present study, a CRT homologue (SsCRT) was cloned, identified and characterized from black rockfish, Sebastes schlegeli, an important aquaculture species in East Asia. The full length of SsCRT cDNA is 2180 bp and encoded a polypeptide of 425 amino acids. SsCRT contains a signal peptide, three distinct structural and functional domains (N-, P- and C-domains), and an endoplasmic reticulum (ER) retrieval signal sequence (KDEL). The deduced amino acid sequence of SsCRT shares 89–92% overall sequence identities with the CRT proteins of several fish species. SsCRT was distributed ubiquitously in all the detected tissues and was highly expressed in the spleen, muscle and liver. After the infection of fish extracellular bacterial pathogen Vibrio anguillarum and intracellular bacterial pathogen Edwardsiella tarda, the mRNA transcripts of SsCRT in spleen, liver, and head kidney were significantly up-regulated. The expression patterns were time-dependent and tissue-dependent. Recombinant SsCRT (rSsCRT) exhibited apparent binding activities against different bacteria and PAMPs. In vivo studies showed that the expressions of multiple immune-related genes such as TNF13B, IL-1β, IL-8, SAA, Hsp70, and ISG15 in head kidney were significantly enhanced when black rockfish were treated with rSsCRT. Furthermore, rSsCRT reduced pathogen dissemination and replication in fish kidney and spleen. These results indicated that SsCRT served as an immune receptor to recognize and eliminate the invading pathogens, which played a vital role in the immune response of Sebastes schlegeli . These findings provide new insights into understanding the roles of CRT proteins in immune response and pathogen infection in teleost. Highlights: SsCRT contained three distinct functional domains and an ER retrieval KDEL. SsCRT expression was upregulated upon extracellular and intracellular bacterial infection. rSsCRT bound to different bacteria and PAMPs in vitro. rSsCRT increased the capability of host cells to defense against pathogen infection. rSsCRT enhanced the expressions of immune related genes.